In Whose Interest? : The Privatisation of Child Protection and Social Work - Jones, Ray, 1949- (Book collections on Project MUSE., 2019)
"As the government continues to open up child protection and social work in England to a commercial market place, what is the social cost of privatising public services? And what effect has the failure of previous privatisations had on their provision? This book, by best-selling author and expert social worker Ray Jones, is the first to tell the story of how crucial social work services, including those for families and children, are now being out-sourced to private companies. Detailing how the failures of previous privatisations have led to the deterioration of services for the public, it shows how this trend threatens the safety and wellbeing of vulnerable children and disabled adults."--Page 4 of cover.